2020
DOI: 10.3390/cells9061520
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Mitochondrial Calcium Uniporter at the Whole-Cell and Single Mitochondrion Levels in WT, MICU1 KO, and MICU2 KO Cells

Abstract: Mitochondrial Ca2+ ([Ca2+]M) uptake through its Ca2+ uniporter (MCU) is central to many cell functions such as bioenergetics, spatiotemporal organization of Ca2+ signals, and apoptosis. MCU activity is regulated by several intrinsic proteins including MICU1, MICU2, and EMRE. While significant details about the role of MICU1, MICU2, and EMRE in MCU function have emerged recently, a key challenge for the future experiments is to investigate how these regulatory proteins modulate mitochondrial Ca2+ influx through… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Interestingly, it is involved in the mild stress-induced mitochondria hyperfusion as a pro-survival response, acting in synergy with OPA1, a protein that is required for mitochondrial fusion and which was highly expressed in PXE mitochondria. Cell energy metabolism, ROS production, and calcium homeostasis, besides STML2, are further modulated by the overexpression of MCU, a calcium uniporter protein acting as a primary mediator of Ca 2+ influx into the mitochondria (Takeuchi et al, 2015) through a process dependent on the membrane potential of the inner mitochondrial membrane (Shah and Ullah, 2020). It is to be noted that MCU allows rapid and massive Ca 2+ entry at high cytosolic Ca 2+ concentrations (>10 µM).…”
Section: Shotgun Proteomics Analysis Reveals Changes In Mitochondrialmentioning
confidence: 99%
“…Interestingly, it is involved in the mild stress-induced mitochondria hyperfusion as a pro-survival response, acting in synergy with OPA1, a protein that is required for mitochondrial fusion and which was highly expressed in PXE mitochondria. Cell energy metabolism, ROS production, and calcium homeostasis, besides STML2, are further modulated by the overexpression of MCU, a calcium uniporter protein acting as a primary mediator of Ca 2+ influx into the mitochondria (Takeuchi et al, 2015) through a process dependent on the membrane potential of the inner mitochondrial membrane (Shah and Ullah, 2020). It is to be noted that MCU allows rapid and massive Ca 2+ entry at high cytosolic Ca 2+ concentrations (>10 µM).…”
Section: Shotgun Proteomics Analysis Reveals Changes In Mitochondrialmentioning
confidence: 99%
“…This impaired Ca 2+ uptake resulted in structural changes including forming short tubular mitochondria. MICU1 knockout was not rescued by increased expression of MCU [35,37,62,63].…”
Section: Micu1 Functionmentioning
confidence: 93%
“…MICU1 knockout in islet β cells resulted in structural changes, including the formation of short tubular mitochondria. Increased expression of MCU did not rescue the results brought by MICU1 knockout 85 . Another study showed that siRNA‐mediated knockdown of MICU2 in islet β cell reduced insulin secretion by 41%–51% 54 .…”
Section: Pathological Role Of Mcu Complex In Metabolic Diseasesmentioning
confidence: 96%
“…Increased expression of MCU did not rescue the results brought by MICU1 knockout. 85 Another study showed that siRNA-mediated knockdown of MICU2 in islet β cell reduced insulin secretion by 41%-51%. 54 Similarly, mitochondrial Ca 2+ uptake is attenuated, and the electron transport chain (ETC) is not stimulated, and ATP is not transported to the cell membrane to close K + channels.…”
Section: Mcu Complex In Diabetesmentioning
confidence: 99%